2018
DOI: 10.1186/s12876-018-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ2 and -DQ8 genotype frequency in Syrian celiac disease children: HLA-DQ relative risks evaluation

Abstract: BackgroundCeliac disease (CD) is a common autoimmune disease in Syria which manifesting with inflammation of the small intestine and with various extra intestinal symptoms. The disease is associated with human HLA-DQ genes encoding HLA-DQ2 and DQ8 proteins.MethodsIn this study, 49 children patients of CD and 58 healthy control samples were genotyped for HLA-DQ genes using SSP-PCR technique. Relative risks for different genotypes were also evaluated.ResultsThe DQB1*0201 allele was the most common in the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
5
9
0
1
Order By: Relevance
“…Our results shows that, in total 67.3% of Saudi CD patients were predicted to be the carriers of HLA CD-associated major risk alleles. We observed that Saudi individuals with homozygous HLA- DQ2.5 haplotype have a 4-fold higher risk to develop CD (OR = 4.074).This finding further confirms previous studies, which revealed a high risk associated with two copies of DQ2.5 among Europeans, Africans and Arabs ( Table 5 ) [ 17 , 22 , 24 , 27–31 ]. A recent study among Saudi children has reported that the homozygous DQ2.5 was seen in more CD cases than healthy controls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results shows that, in total 67.3% of Saudi CD patients were predicted to be the carriers of HLA CD-associated major risk alleles. We observed that Saudi individuals with homozygous HLA- DQ2.5 haplotype have a 4-fold higher risk to develop CD (OR = 4.074).This finding further confirms previous studies, which revealed a high risk associated with two copies of DQ2.5 among Europeans, Africans and Arabs ( Table 5 ) [ 17 , 22 , 24 , 27–31 ]. A recent study among Saudi children has reported that the homozygous DQ2.5 was seen in more CD cases than healthy controls.…”
Section: Discussionsupporting
confidence: 90%
“…The DQ2.2 haplotype is a low risk haplotype in CD patients in many countries [ 21 , 24 , 41 , 42 ]. In our study, predicted homozygous DQ2.2 was more frequent in control group (5.82%) than in cases (0.99%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous small studies from India have reported absence of these two DQ antigens in 6–16% of patients with CeD 20–22 . Small studies in other populations indicate the absence of DQ2 and/or DQ8 in 12–35% of CeD patients 23–25 . Studies now indicate that other HLA‐DQ antigens, including DQ7 and DQ9, may confer risk to CeD 26,27 …”
Section: Discussionmentioning
confidence: 97%
“…After this publication, rare study has appeared, is the case of Almeida et al [2] and Murad et al [64], that given the existence of the estimated prevalence of these populations in other studies in the same region, were able to calculate the CD risk development in the populations of Brazil and Syria, respectively.…”
Section: Hla and The Importance Of Risk Genotypes In Laboratory Genotmentioning
confidence: 99%
“…Murad et al [64] found in the Syrian population, a slightly different risk for DQ2.5/DQ2.5, DQ2.5/DQ2.2, and DQ2.5/DQ8 genotypes and the associated risks were, respectively, 1:12.5, 1:20, and 1:10, emphasizing that in this population of origin other than Caucasians, the risk associated to these genotypes are somewhat different in terms of prevalence, but they continue to confer the greatest risks for developing CD (Figures 2 and 3). Because it is not possible to calculate the risk for the various world populations, there are many where the absence of disease prevalence data does not allow this calculation to be carried out, an estimate for populations of Caucasian origin seems to produce very close results suggesting that calculations are accurate in these populations.…”
Section: Hla and The Importance Of Risk Genotypes In Laboratory Genotmentioning
confidence: 99%